Comparison between Vaginal and Oral Misoprostol for the Induction of Labour in Patients with Intrauterine Fetal Death - Sharmin, Susmita; Naznin, Farhana; Akter, Nurjahan; Begum, Bedowra; Jesmin, Shahela; Khatun, Rokeya (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: A woman may need to give birth prior to the spontaneous onset of labour in situations where the fetus has died in utero or for the termination of pregnancy where the fetus, if born alive would not survive or would have a permanent handicap. Misoprostol is a prostaglandin medication that can be used to induce labour in these situations. But there is widespread dispute as to which route of administration to be preferred in terms of efficacy and safety. The present study was intended to compare the oral and vaginal misoprostol in the termination of pregnancy with intrauterine foetal death (IUFD). Methods: This randomized clinical trial (RCT) was carried out in the Department of Obstetrics & Gynecology, Rajshahi Medical College & Hospital (RMCH) over a period of 12 months from July 2018 to June 2019. Pregnant women with established IUFD after 28 weeks of gestation were the study population. A total of 108 such patients were included in the study and were randomly and equally allocated into Oral Misoprostol (OM) and Vaginal Misoprostol (VM) Groups to receive either tablet misoprostol 100 μg orally or tablet misoprostol 100 μg via vaginal route. The outcome measures were successful delivery within 24 hours following induction, induction to delivery interval and induction to pain interval. The maternal safety was evaluated in terms of incidences of side-effects and complications. Result: In the present study all cases of IUFD delivered successfully and there was no case of failed induction. The comparative evaluation between oral and vaginal misoprostol in the management of IUFD demonstrated that the induction to delivery interval and induction to labour pain interval both were significantly lower in VM Group than those in OM Group (p < 0.001 and p < 0.001 respectively). The amount of misoprostol needed was also lower in the former group than that in the latter group (p < 0.001). The incidence of side-effects like nausea was significantly lower in VM Group than that in OM Group (p = 0.001), while vomiting was completely absent in the VM group (p = 0.013). There was no incidence of pyrexia in the VM Group. Conclusion: The study concluded that oral misoprostol for induction of labour for termination of pregnancy in the third trimesters following IUFD is comparatively less effective than vaginal misoprostol, with women experiencing a longer induction to birth interval. The incidence of side-effects (nausea, vomiting and pyrexia) is also more in the oral misoprostol group. Ibrahim Card Med J 2021; 11 (2): 56-61